3D Tissue Microarray Controls: A Potential Standardization Solution. Issue 9 (October 2018) - Myers, Charles W.; Bhimji-Patel, Sonal; Rees, Mark; Imam, Syed Ashraf; Cohen, Cynthia
Abstract : The use of controls is a hallmark for quality control in anatomic pathology. However, standardization of controls between laboratories has been a significant issue. Differential processing techniques between institutions and a multitude of preanalytical difficulties can result in different immunostain intensities. So called histoid controls, xenografts or culture cell lines, have been discussed in the past but with no recent followup. Herein is presented a histoid termed a 3D tissue microarray control (3D TMAC) control to help alleviate the burgeoning need for control standardization. A breast and cervix 3D TMAC control were tested for staining quality for 11 different antibodies commonly tested in either breast or cervical cancer work ups. We additionally looked at a small run of 5 days of CK5 and HER2 for reproducibility of the 3DRSTMA. Staining quality of 9 of the antibodies stained appropriately and 2 stained inappropriately, mammoglobin and GCDFP. Two of the antibodies were not reported to have any staining properties in the 3D TMAC, p16 and mammoglobin. Of these, p16 had appropriate staining and mammoglobin did not. In the 5 runs of CK5 and HER2, there was good reproducibility between stains assessed by both visual and computer-assisted methods, with membrane intensity coefficients of variation of 3.58% and 3.18%, respectively. The 3D TMAC has the potential to markedly improve intralaboratory and interlaboratory standardization practices.